THE COLORISTIC MODEL OF THE WORLD IN DARIA MELNYKOVYCH-RYKHTYTSKA’S LYRICS - Машталер, О. О. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals the problem of synthesis of arts of painting and poetry in Daria Rykhtytska’s lyrics. The work pays attention to understanding the processes of aesthetic space on the basis of verbal modeling of nonverbal arts. The ways of nascence of associative clutch of components of related arts, their combination are revealed. The specifics of the writer’s artistic thinking, based on the crossbreeding of several arts are researched.